A new high-quality elderberry plant extract exerts antiviral and immunomodulatory effects in vitro and ex vivo. Issue 1 (1st January 2021) - Schön, Christiane; Mödinger, Yvonne; Krüger, Franziska; Doebis, Cornelia; Pischel, Ivo; Bonnländer, Bernd
ABSTRACT: Infections of the respiratory system, including common cold and influenza, are affecting people worldwide and are more or less prone to spread depending on the season and viral load of the host. For reducing symptoms and duration of illness, treatment options to standard prescribed drugs are in demand. Natural products could provide immune-supporting treatment alternatives. Elderberry extracts have been used in traditional medicine for the treatment of respiratory infections for decades and numerous studies describe the beneficial effects of elderberries on the immune system and respiratory infectious disease. We investigated the immunomodulative and antiviral effects of a high-quality, anthocyanin-enriched elderberry fruit extract (eldosamb®). Results reveal that elderberry extract reduced the secretion of pro-inflammatory cytokines TNF-α and IFN-γ, leading to a shift towards the Th2-Helper cell response and showing antiviral efficacy against the MVA virus. Thus, with its anti-inflammatory and antiviral bioactivity the proprietary elderberry extract suggests its use as an immunomodulatory health product.